ANALISYS PROFITABILITY REFILL MINERAL WATER ON SISKA BUSINESS IN SANGATTA - Gazali, Sayid Firdaus (EKONOMIA, 2013)
The purpose this research is to determine the profitability growth refill mineral water on Siska business. The research was conducted for 1 month (May to June 2013) on the Business Siska in Sangatta, relating to profitability in 2012 compared to 2011. Research activities carried out are: literature study, field observations, interviews, documentation, data collection and analysis. Data collected in the study covers: Overview of firms, the cost of production, profit and loss, sales policy. Data analysis instrument use rentbility Ratio Analysis covers: Profit Margin, Net Profit Margin, Return on Assets, Return on Equity and Return on Investment. Research results show profit margin = 21.23% in 2012 compared to 2011 = 14.59% 45.51% growth, net profit margin in 2012 = 15.93% 2011 = 10.94 compared to 45.61% growth, Return on Assets = 12.17% in 2012 compared to 2011 = 8.08% experienced growth of 50.62%, Return on Equity = 10.36 in 2012 compared to 2011 = 7.11% 45.71% growth and return on Investment = 9.13% in 2012 compared to 2011 = 6.06 50.66% growth.Â